The modification of the perforated plate in the fluidized-bed combustor to analyze heat convection rate and temperature - Erdiwansyah, .; Mahidin, .; Husni, Husin; Muhammad Faisal, .; Muhtadin, .; Asri, Gani; R. E., Sardjono; Rizalman, Mamat (Hindawi, 2021)
Investigation of combustion temperature through experiments with a wide range of fuels, both solid and liquid, is continuously being conducted by scientists around the world, while the measurement of heat transfer rate can be analyzed when the combustion process occurs. Previous research has generally been conducted using liquefied gas, fossil fuels, and alcohol additives. Specifically, the research in this work investigated the convection heat rate and combustion temperature through the modification of the perforated plate. The experiment was conducted in the fluidized-bed combustor (FBC) fuel chamber using solid waste fuel of oil palm biomass. Measurements were performed at four different points using the HotTemp HT-306 Digital Thermometer. The results of the experiment showed that the convection heat rate in measurement one (M-I) reached 8.258 W/m2 for palm kernel shell (PKS) fuel. Meanwhile, in measurement two (M-II), the convection rate of 7.392 W/m2 was produced by oil palm midrib (OPM) fuel. The highest combustion temperature was recorded with OPM fuel (884°C) at M-I. However, the combustion temperature of the PKS combustion process is higher at 896°C but shows a less good trend than OPM. Overall, the measurement results of the three types of fuel used to modify the perforated plate applied in the FBC fuel chamber are excellent. It can be proven that the fuel is put into the combustion chamber with nothing left.